2008
DOI: 10.1071/en08047
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for marine production of monoterpenes

Abstract: Environmental context. Laboratory incubation experiments and shipboard measurements in the SouthernAtlantic Ocean have provided the first evidence for marine production of monoterpenes. Nine marine phytoplankton monocultures were investigated using a GC-MS equipped with an enantiomerically-selective column and found to emit monoterpenes including (−)-/(+)-pinene, limonene and p-ocimene, all of which were previously thought to be exclusively of terrestrial origin. Maximum levels of 100-200 pptv total monoterpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(202 citation statements)
references
References 40 publications
11
185
5
1
Order By: Relevance
“…As already discussed, mixing ratios of isoprene (Sinha et al, 2007;Yassaa et al, 2008) and monoterpenes (Yassaa et al, 2008) have been reported to reach in the region of hundreds of pptv over active phytoplankton blooms in the marine boundary layer. Additionally, the emission of small alkenes from coastal waters has been observed (Lewis et al, 1999).…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…As already discussed, mixing ratios of isoprene (Sinha et al, 2007;Yassaa et al, 2008) and monoterpenes (Yassaa et al, 2008) have been reported to reach in the region of hundreds of pptv over active phytoplankton blooms in the marine boundary layer. Additionally, the emission of small alkenes from coastal waters has been observed (Lewis et al, 1999).…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 98%
“…While the vast majority of these emissions are from terrestrial sources, there are also biogenic emissions in coastal and remote marine environments, associated with seaweed and phytoplankton blooms (Moore et al, 1994). Isoprene mixing ratios (as well as those of some monoterpenes) have been reported to reach hundreds of pptv (parts per trillion by volume) over active phytoplankton blooms in the marine boundary layer (Sinha et al, 2007;Yassaa et al, 2008), with the potential to impact local air quality (Williams et al, 2010). Removal of isoprene from the troposphere is dominated by reaction with the OH radical during the day and reaction with the nitrate radical during the night (Calvert et al, 2000).…”
Section: Isoprene Ozonolysismentioning
confidence: 99%
“…Such a large source would produce atmospheric isoprene concentrations over the remote oceans orders of magnitude larger than observed. These findings suggest a nondominant role for isoprene in driving OC abundances in the remote Southern Ocean, implying an alternative source from primary OC aerosol emission or oxidation of other ocean-emitted volatile organics such as monoterpenes (Yassaa et al, 2008).…”
Section: Conclusion and Recommendationsmentioning
confidence: 94%
“…Assuming an OH concentration of 3 × 10 6 molec/cm 3 and an atmospheric life time of CHO-CHO of 2 h (conservative upper limit), the VOC concentration needed to explain 100 ppt of CHOCHO is either 600 ppt of isoprene, 2.8 ppb toluene, or 8.9 ppb acetylene, or lower concentrations if multiple compounds were present. There are few observations of VOCs over the remote open ocean, and most of them focus on isoprene (Bonsang et al, 1992;Broadgate et al, 1997Broadgate et al, , 2004Baker et al, 2000;Matsunaga et al, 2002;Meskhidze and Nenes, 2006;Yassaa et al, 2008). The currently measured isoprene concentrations do not exceed 40 ppt and mostly are on the order of 10 ppt.…”
Section: Discussionmentioning
confidence: 99%